Pharmacokinetics of fluconazole after oral administration to healthy beagle dogs. Issue 6 (24th August 2022) - Choi, Yujin; Koo, Yoonhoi; Yun, Taesik; Chae, Yeon; Lee, Dohee; Jeong, Jong‐Woo; Lee, Kyeong‐Ryoon; Kim, Hakhyun; Yang, Mhan‐Pyo; Kang, Byeong‐Teck
Abstract: Background: Fluconazole can be effective in the treatment of superficial mycoses in dogs. However, the pharmacokinetics of fluconazole have not yet been evaluated to determine its optimal dosing regimen. Objectives: This study aimed to determine the plasma concentration of fluconazole after single and multiple administrations at two different dosages in dogs. Methods and materials: Eight healthy beagle dogs were divided into two groups, and each group received either 5 or 10 mg/kg of fluconazole per os. The pharmacokinetics of fluconazole was determined following single and multiple administrations p.o. Single‐ and multiple‐dose treatment periods were separated by a washout period of seven days. Plasma concentrations of fluconazole were determined by established high‐performance liquid chromatography coupled with tandem mass spectrometry system. Results: In the 5 mg/kg group, the mean maximum concentrations ( C max ) and the area under the plasma concentrations (AUC0‐24h ) were 4.84 μg/mL and 85.56 μg*h/mL, respectively, after single administration and 6.58 μg/mL and 119.52 μg*h/mL, respectively, after multiple administrations. In the 10 mg/kg group, the C max and AUC0‐24h were 5.67 μg/mL and 109.19 μg*h/mL, respectively, after single administration and 15.10 μg/mL and 291.51 μg*h/mL, respectively, after multiple administrations. The C max ( p  < 0.001) and AUC0‐24h ( p  < 0.001) were significantly lower in the 5 mg/kg group than those in the 10 mg/kg group at multiple administrations. Conclusions and clinical relevance: Fluconazole accumulates in plasma and exhibits dose‐proportional pharmacokinetics after multiple doses, and was safe and well tolerated at these doses for short‐term administration. Abstract : Background – Fluconazole is effective in the treatment of superficial mycoses in dogs. However, the pharmacokinetics of fluconazole has not yet been evaluated to determine its optimal dosing regimen. Objectives – This study aimed to determine the plasma concentration of fluconazole after single and multiple administrations at two different dosages in dogs. Conclusions and clinical relevance – Fluconazole accumulates in plasma and exhibits dose‐proportional pharmacokinetics after multiple doses, and was safe and well tolerated at these doses for short‐term administration. Résumé: Contexte: Le fluconazole est efficace dans le traitement des mycoses superficielles chez le chien. Cependant, la pharmacocinétique du fluconazole n'a pas encore été évaluée pour déterminer son schéma posologique optimal. Objectifs: Cette étude visait à déterminer la concentration plasmatique de fluconazole après des administrations uniques et multiples à deux doses différentes chez le chien. Méthodes et matériel: Huit chiens beagle sains ont été divisés en deux groupes, et chaque groupe a reçu 5 ou 10 mg/kg de fluconazole per os . La pharmacocinétique du fluconazole a été déterminée après des administrations uniques et multiples p.o. Les périodes de traitement à dose unique et à doses multiples ont été séparées par une période de sevrage de sept jours. Les concentrations plasmatiques de fluconazole ont été déterminées par chromatographie liquide à haute performance couplée à un système de spectrométrie de masse en tandem. Résultats: Dans le groupe 5 mg/kg, les concentrations maximales moyennes ( C max ) et l'aire sous les concentrations plasmatiques (ASC0‐24h) étaient respectivement de 4, 84 μg/mL et 85, 56 μg*h/mL après administration unique et de 6, 58 μg /mL et 119, 52 μg*h/mL, respectivement, après plusieurs administrations. Dans le groupe 10 mg/kg, la C max et l'ASC0‐24h étaient de 5, 67 μg/mL et 109, 19 μg*h/mL, respectivement, après une administration unique et de 15, 10 μg/mL et 291, 51 μg*h/mL, respectivement, après plusieurs administrations. La C max ( p < 0, 001) et l'ASC0‐24h ( p < 0, 001) étaient significativement plus faibles dans le groupe 5 mg/kg que celles du groupe 10 mg/kg lors d'administrations multiples. Conclusions et pertinence clinique: Le fluconazole s'accumule dans le plasma et présente une pharmacocinétique proportionnelle à la dose après plusieurs doses, et était sûr et bien toléré à ces doses pour une administration à court terme. Resumen: Introducción: el fluconazol es efectivo en el tratamiento de micosis superficiales en perros. Sin embargo, la farmacocinética de fluconazol aún no ha sido evaluada para determinar su régimen de dosificación óptimo. Objetivos: Este estudio tuvo como objetivo determinar la concentración plasmática de fluconazol después de administraciones únicas y múltiples en dos dosis diferentes en perros. Métodos y materiales: ocho perros Beagle sanos se dividieron en dos grupos y cada grupo recibió 5 o 10 mg/kg de fluconazol por vía oral. La farmacocinética de fluconazol se determinó tras administraciones únicas y múltiples p.o. Los períodos de tratamiento de dosis única y múltiple estuvieron separados por un período de lavado de siete días. Las concentraciones plasmáticas de fluconazol se determinaron mediante cromatografía líquida de alta resolución establecida junto con un sistema de espectrometría de masas en tándem. Resultados: En el grupo de 5 mg/kg, las concentraciones máximas medias (Cmax) y el área bajo la curva de las concentraciones plasmáticas (AUC 0‐24h ) fueron 4, 84 μg/mL y 85, 56 μg*h/mL, respectivamente, después de una sola administración y 6, 58 μg /mL y 119, 52 μg*h/mL, respectivamente, después de múltiples administraciones. En el grupo de 10 mg/kg, la Cmax y AUC 0‐24h fueron 5, 67 μg/mL y 109, 19 μg*h/mL, respectivamente, después de una sola administración y 15, 10 μg/mL y 291, 51 μg*h/mL, respectivamente, después de múltiples administraciones . La Cmax ( p < 0, 001) y el AUC 0‐24h (p < 0, 001) fueron significativamente inferiores en el grupo de 5 mg/kg que en el grupo de 10 mg/kg en administraciones múltiples. Conclusiones y relevancia clínica: el fluconazol se acumula en el plasma y exhibe una farmacocinética proporcional a la dosis después de múltiples dosis, y fue seguro y bien tolerado a estas dosis para la administración a corto plazo. Zusammenfassung: Hintergrund: Fluconazol ist bei der Behandlung von oberflächlichen Mykosen bei Hunden wirksam. Die Pharmakokinetik von Fluconazol wurde jedoch bisher noch nicht in Bezug auf ein optimales Dosisregime evaluiert. Ziele: Diese Studie zielte darauf ab, Plasmakonzentrationen von Fluconazol nach einmaliger oder mehrmaliger Verabreichung in zwei unterschiedlichen Dosierungen bei Hunden festzustellen. Methoden und Materialien: Acht gesunde Beagles wurden in zwei Gruppen eingeteilt, wobei jede Gruppe entweder 5 oder 10 mg/kg Fluconazol per os erhielt. Die Pharmakokinetik von Fluconazol wurde nach der einmaligen oder nach mehrmaliger Administration p.o . bestimmt. Einmalige und multiple Behandlungsperioden wurde durch eine Auswaschzeit von sieben Tagen unterbrochen. Die Plasmakonzentrationen von Fluconazol wurden mittels einer etablierten Hochleistungsflüssigkeitschromatografie gekoppelt mit einem Tandem Massenspektrometrie System bestimmt. Ergebnisse: In der 5 mg/kg Gruppe lag die durchschnittliche Maximale Konzentration (Cmax ) und die Fläche unter den Plasmakonzentrationen (AUC0‐24h ) nach einmaliger Applikation bei 4, 84 μg/mL beziehungsweise 85, 56 μg*h/mL und nach multiplen Verabreichungen bei 6, 58 μg/mL beziehungsweise 119, 52 μg*h/mL. In der 10 mg/kg Gruppe lagen die Cmax und die AUC0‐24h nach einer einzigen Verabreichung bei 5, 67 μg/mL beziehungsweise 109, 19 μg*h/mL und bei multipler Verabreichung bei 15, 10 μg/mL beziehungsweise 291, 51 μg*h/mL. Die Cmax ( p < 0, 001) und AUC0‐24h ( p < 0, 001) waren für multiple Verabreichungen in der 5 mg/kg Gruppe signifikant niedriger als in der 10 mg/kg Gruppe. Schlussfolgerungen und klinische Bedeutung: Fluconazol akkumuliert in Plasma und zeigt nach multiplen Dosen eine Dosis‐abhängige Pharmakokinetik; es war sicher und wurde bei diesen Dosierungen für eine Kurzzeitverabreichung gut toleriert. 要約: 背景: フルコナゾールは犬の表在性真菌症に有効である。しかし、フルコナゾールの薬物動態は未解明であり、最適な投与方法を検討する必要がある。 目的: 本研究では、犬において2種類の投与量で単回および複数回投与した際のフルコナゾールの血漿中濃度を測定することを目的とした。 材料および方法: 健常ビーグル犬8頭を2群に分け、各群にフルコナゾールを1回当たり5 mg/kgまたは10 mg/kg投与した。単回投与および反復投与は7日間のウォッシュアウト期間を設けて実施した。血漿中濃度は、高速液体クロマトグラフィー/タンデム質量解析計を用いて測定した。 結果: 5 mg/kg群では、単回投与時の平均最高濃度(Cmax)および血漿中濃度下面積(AUC0‐24h)はそれぞれ4.84 μg/mL、85.56 μgh/mL、反復投与時はそれぞれ6.58 μg/mL、119.52 μgh/mLであった。10 mg/kg群では、単回投与時のCmaxおよびAUC0‐24hはそれぞれ5.67 μg/mL、109.19 μgh/mL、反復投与時はそれぞれ15.10 μg/mL，291.51 μgh/mLであった。また、複数回投与時のCmax(p<0.001)およびAUC0‐24hは、5 mg/kg群が10 mg/kg群に比べ有意に低かった(p<0.001)。 結論および臨床的意義: フルコナゾールは、血漿中に蓄積され、複数回投与により用量比の薬物動態を示し、これらの用量での短期投与は安全で忍容性が高いことが確認された。 摘要: 背景: 氟康唑可有效治疗犬浅层真菌病。然而，尚未评价氟康唑的药代动力学以确定其最佳给药方案。 目的: 本研究旨在测定犬单次和多次给予两种不同剂量氟康唑后的血浆浓度。 方法和材料: 8只健康比格犬分为两组，每组经口给予氟康唑5或10 mg/kg。在单次和多次p.o.给药后测定氟康唑的药代动力学。单次和多次给药治疗阶段之间间隔7天的洗脱期。采用建立的高效液相色谱串联质谱系统测定氟康唑的血药浓度。 结果: 在 5 mg/kg 给药组中，单次给药后的平均最大浓度 (Cmax) 和血浆浓度下面积 (AUC0‐24 h) 分别为4.84 μg/mL和85.56 μg h/mL，多次给药后分别为6.58 μg/mL和119.52 μg h/mL。在 10 mg/kg 给药组中，单次给药后的 Cmax 和 AUC0‐24 h 分别为5.67 μg/mL和109.19 μg h/mL，多次给药后的 Cmax 和 AUC0‐24 h 分别为15.10 μg/mL和291.51 μg h/mL。多次给药时，5 mg/kg组的Cmax(p < 0.001) 和AUC0‐24 h(p < 0.001) 显著低于 10 mg/kg 组。 结论和临床相关性: 氟康唑在血浆中蓄积，多次给药后表现出与剂量成比例的药代动力学，在这些剂量下短期给药安全且耐受性良好。 Resumo: Contexto: Fluconazol é um tratamento eficaz para micoses superficiais em cães. Entretanto, a farmacocinética do fluconazol ainda não foi avaliada para determinar o regime de doses ideal. Objetivos: Este estudo teve por objetivo determinar a concentração plasmática de fluconazol após administrações únicas e múltiplas em duas dosagens diferentes em cães. Métodos e materiais: Oito cães saudáveis da raça Beagle foram divididos em dois grupos, e cada grupo recebeu 5 ou 10 mg/kg de fluconazol por via oral. A farmacocinética de fluconazol foi determinada seguindo administrações únicas ou múltiplas por via oral. Os protocolos de tratamento em doses únicas ou múltiplas foram separados por um intervalo de sete dias. As concentrações plasmáticas de fluconazol foram determinadas por cromatografia líquida de alta eficiência acoplada ao sistema de espectrometria de massa em tandem. Resultados: No grupo de 5mg/kg, as concentrações máximas médias ( C max ) e as áreas abaixo das curvas de concentrações plasmáticas (AUC0‐24h ) foram 4, 84 μg/mL e 85, 56 μg*h/mL, respectivamente, após administrações únicas e 6, 58 μg/mL e 119, 52 μg*h/mL, respectivamente, após administrações múltiplas. No grupo de 10mg/kg, C max e AUC0‐24h foram 5, 67 μg/mL E 109, 19 μg*h/mL, respectivamente, após administrações múltiplas. C max ( p  < 0, 001) e AUC0‐24h ( p  < 0, 001) foram significativamente mais baixas no grupo 5 mg/kg que no grupo 10 mg/kg em administrações múltiplas. Conclusões e relevância clínica: O fluconazol se acumula no plasma e exibe farmacocinética proporcional à dose após múltiplas doses, e foi seguro e bem tolerado nessas doses para administração em curto prazo.